Rhizosphere microorganisms of Crocus sativus as antagonists against pathogenic Fusarium oxysporum - Zhang, Jiahao; Lu, Jiemiao; Zhu, Yichun; Huang, Qinger; Qin, Luping; Zhu, Bo (Frontiers in Plant Science, 2022)
Several microorganisms in the plant root system, especially in the rhizosphere, have their own compositions and functions. Corm rot is the most severe disease of Crocus sativus, leading to more than 50% mortality in field production. In this study, metagenomic sequencing was used to analyze microbial composition and function in the rhizosphere of C. sativus for possible microbial antagonists against pathogenic Fusarium oxysporum. The microbial diversity and composition were different in the C. sativus rhizosphere from different habitats. The diversity index (Simpson index) was significantly lower in the C. sativus rhizospheric soil from Chongming (Rs_CM) and degenerative C. sativus rhizospheric soil from Chongming (RsD_CM) than in others. Linear discriminant analysis effect size results showed that differences among habitats were mainly at the order (Burkholderiales, Micrococcales, and Hypocreales) and genus (Oidiodendron and Marssonina) levels. Correlation analysis of the relative lesion area of corm rot showed that Asanoa was the most negatively correlated bacterial genus (ρ = −0.7934, p < 0.001), whereas Moniliophthora was the most negatively correlated fungal genus (ρ = −0.7047, p < 0.001). The relative lesion area result showed that C. sativus from Qiaocheng had the highest resistance, followed by Xiuzhou and Jiande. C. sativus groups with high disease resistance had abundant pathogen resistance genes, such as chitinase and β-1,3-glucanase genes, from rhizosphere microorganisms. Further, 13 bacteria and 19 fungi were isolated from C. sativus rhizosphere soils, and antagonistic activity against pathogenic F. oxysporum was observed on potato dextrose agar medium. In vivo corm experiments confirmed that Trichoderma yunnanense SR38, Talaromyces sp. SR55, Burkholderia gladioli SR379, and Enterobacter sp. SR343 displayed biocontrol activity against corm rot disease, with biocontrol efficiency of 20.26%, 31.37%, 39.22%, and 14.38%, respectively. This study uncovers the differences in the microbial community of rhizosphere soil of C. sativus with different corm rot disease resistance and reveals the role of four rhizospheric microorganisms in providing the host C. sativus with resistance against corm rot. The obtained biocontrol microorganisms can also be used for application research and field management.